2019
DOI: 10.1016/j.bone.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass development is sensitive to insulin resistance in adolescent boys

Abstract: declare that they have no conflict of interest. Highlights  Insulin resistance was inversely associated with bone mass in adolescent boys  The association in boys was not explained by differences in body composition or physical activity levels  No association between insulin resistance and bone mass was observed in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Despite a clear association between T2D and increased fracture risk[9,19,24], evidence supporting an association between prediabetes and fracture risk is inconsistent. Observations in adolescents suggest that insulin resistance may be detrimental for bone development through puberty, independent of body composition and the level of physical activity[25]. However, no association between insulin resistance and fracture risk was evident after adjustment for BMI and bone mineral density (BMD) in a large cohort of elderly subjects[26].…”
Section: Diabetes and Prediabetes: Clinical Impact On Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Despite a clear association between T2D and increased fracture risk[9,19,24], evidence supporting an association between prediabetes and fracture risk is inconsistent. Observations in adolescents suggest that insulin resistance may be detrimental for bone development through puberty, independent of body composition and the level of physical activity[25]. However, no association between insulin resistance and fracture risk was evident after adjustment for BMI and bone mineral density (BMD) in a large cohort of elderly subjects[26].…”
Section: Diabetes and Prediabetes: Clinical Impact On Bonementioning
confidence: 99%
“…Preclinical studies[25] documented alterations in transcription of osteoblasts promoting genes, in particular Runx2, which is involved in MSC differentiation into pre-OBs and in the regulation of bone matrix protein genes. Some preclinical studies suggested that Runx2 is downregulated by hyperglycemia[35,36], although other studies reported no modification[37,38].…”
Section: Diabetic Bone Disease-pathophysiologymentioning
confidence: 99%
“…Furthermore, a recent clinical study in girls and boys aged 10e17 years showed an inverse association between the homeostasis model assessment of insulin resistance in boys and total body BMC. The association was independent of body composition, levels of osteocalcin or physical activity [28]. Insulin resistance seems to be mediating the negative association between adiposity and lumbar spine bone mass in children, as estimated in a sample of 240 children aged 7e15 years [29].…”
Section: Discussionmentioning
confidence: 82%
“…A mouse model showed that hyperinsulinemia and insulin resistance caused reduced bone turnover and led to increased bone fragility by increasing cortical porosity or other defects in bone microarchitecture ( 40 ). A longitudinal study showed that insulin resistance may be detrimental to bone development through puberty in boys ( 41 ). Thus, insulin resistance in offspring caused by high fructose during pregnancy may be one of the mechanisms that inhibit bone growth and development in offspring.…”
Section: Discussionmentioning
confidence: 99%